(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Population factors play a significant role in geographical research since they serve as the basis for many other geographical considerations. An essential factor that obstructs regional management and development planning is demographic features. This study is considered in relation to several facets of the population in Karad City, which is well-known to be the centre of religious, social, and intellectual movements as also the centre of political and economic development in the country from ancient times. And also famous for the meeting of the two holy rivers, the Krishna and Koyna. The city of Karad is located in the Satara district, which is part of Maharashtra, India’s Pune division. It is located on the eastern edge of Maharashtra’s Konkan region. Only the most recent two decades have seen a decrease in the population of Karad, which has expanded over the evaluation period of 100 years. At the time of the investigation, different castings have been seen in this group. In terms of percentage, literacy is also doing well at 87.67%. Additionally, the societal complexity is demonstrated by the occupational system.